Effect of haemodialysis on metabolism of calcium - Ali J Hashim Al-Saedi; Sabah N Alwachi; Ban Ghassan Abdulhameed (Al Ameen Medical College, 2016)
Background: Secondary hyperparathyroidismis a frequent complication in chronic kidney disease patients, especially those on haemodialysis. The objective of this study is to find the effect of chronic haemodialysis on Calcium, phosphorus, Calcium × phosphorus product, Alkaline phosphatase (ALP) and Parathyroid hormone (PTH) in peripheral blood of a sample of Iraqi patient who were on chronic haemodialysis. Method: One hundred and three patientson haemodialysis were studied from February 2014 to May 2014. To evaluate the effect of duration of dialysis treatment on Parathyroid hormone and other laboratory tests, patients were divided into two groups according to the haemodialysis duration: group 1 (48 patients<1 year on haemodialysis)and group 2 (55 patients ≥ 1-10 year on haemodialysis). Results: Showed no significant differences (p>0.05) in the level of serum calcium, phosphorus, Calcium × phosphorus product, Alkaline phosphatase and Parathyroid hormone between group 1(<1 year on haemodialysis) andgroup2 (≥ 1 year on haemodialysis). No significant association (p>0.05) was found between haemodialysis duration and each of serum phosphorus, Calcium × phosphorus product, Alkaline phosphatase and Parathyroid hormone. Only significant association (p<0.05) was observed between haemodialysis duration and serum calcium level. Conclusion: No significant increase was observed in the Parathyroid hormone level in group haemodialysis ≥ 1 year compared with haemodialysis <1 year. While haemodialysis duration less than a year were significantly more associated with decreased serum calcium compared with longer period of haemodialysis duration were significantly more to be associated with normal serum calcium.